Experimental and numerical investigations on the shear behaviour of recycled railway ballast. (30th August 2019) - Jia, Wenli; Markine, Valeri; Guo, Yunlong; Jing, Guoqing
Highlights: The performance of recycled and fresh ballast mixture was studied. The boundary of recycled ballast mixing ratio was found out. Ballast surface texture was employed in DEM to represent both recycled and fresh ballast. Recycled ballast could be reinforced by fresh ballast addition. Abstract: Ballast degradation is frequently observed under cyclic loading, and results in bearing capacity and drainage problem of ballast track. To keep the stability and safety, periodical maintenances are needed, such as cleaning and replacement, which produce a huge amount of wasted ballast. Thus, reusing the deteriorated ballast can become a considerable method for sustainable railway development and environment protection. One applications is adding the cleaned deteriorated ballast (i.e. recycled ballast) into fresh ballast. Furthermore, it is common situation that applying the mixture of fresh and deteriorated ballast during the railway operation. To study the mechanical behaviour of this mixture and find out the criterion weight proportion of the recycled ballast, a series of large direct shear tests were performed with different weight proportions (0%, 10%, 20%, 30%, 40%, and 50%) of recycled ballast mixed into fresh ballast under different normal stresses (50, 100 and 200 kPa). In addition, a numerical simulation based on discrete element method (DEM) was used to illustrate the shear strength, contact forces, coordination numbers and displacements of ballast particles. Results show that the shear strength reduction of the mixture is insignificant, when mixed with less than 30% recycled ballast. With the recycled ballast proportion increasing, the shear strength and coordination number reduce and the displacements get larger. This research provides a foundation for the application of recycled ballast, and on the other hands, adding fresh ballast can be a solution to reinforce deteriorated ballast bed.